MicroRNA-424-5p Alleviates Isoflurane Anesthesia-Induced Neurotoxicity in Human Embryonic Stem Cell-Derived Neurons by Targeting FASN. (13th July 2022) - Gu, Xiaojiao; Yue, Wei; Xiu, Mingyu; Zhang, Quanyun; Xie, Rufeng
Abstract : Isoflurane (ISO) is a type of anesthetic that might cause neurotoxicity in children. Although miR-424-5p is considerably downregulated in ISO-treated rat brain samples, its physiological role in ISO-induced neuronal injury in human embryonic stem cell-derived neurons remains unknown (hESC-derived neurons). miR-424-5p expression and fatty acid synthase (FASN) in ISO-treated hESC-derived neurons were tested via qRT-PCR. The amount of protein for Bax, Cleaved-caspase-8, Bcl-2, and FASN was investigated through western blot analysis. The viability and apoptosis of hESC-derived neurons were estimated through cell counting kit-8 assessment and TUNEL assay, accordingly. Superoxide dismutase, glutathione, and malondialdehyde levels were discovered via corresponding kits. The contents of inflammatory factors including interleukin-6 and tumor necrosis factor- α were examined by enzyme-linked immunosorbent assays. The combination between FASN and miR-424-5p was resolute via dual-luciferase reporter assessment. After exposure to ISO, induced neurotoxicity and a decreased miR-424-5p production were identified in hESC-derived neurons. Upregulation of miR-424-5p repressed ISO-induced apoptosis and mitigated ISO-induced inflammatory response and oxidative stress in vitro. FASN expression levels were reduced by elevation of miR-424-5p and upregulated after ISO treatment. Mechanically, FASN was directly targeted by miR-424-5p in hESC-derived neurons. Of note, the miR-424-5p elevation-suppressed neuronal apoptosis, inflammatory response, and oxidative stress were countered by upregulation of FASN.